2022
DOI: 10.1016/j.sjbs.2021.10.023
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of mozenavir as a potential drug for SARS-CoV-2 infection via binding multiple drug targets

Abstract: Since the epidemic began in November 2019, no viable medicine against SARS-CoV-2 has been discovered. The typical medication discovery strategy requires several years of rigorous research and development as well as a significant financial commitment, which is not feasible in the face of the current epidemic. Through molecular docking and dynamic simulation studies, we used the FDA-approved drug mezonavir against the most important viral targets, including spike (S) glycoprotein, Transmembrane serine protease 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…7 ). These results were consistent with the RMSD plots for furin-mozenavir, furin-folic acid, and furin-folinic acid complexes [ 94 , 96 ]. However, same observation cannot be said about the unbound protein as the RMSD continued to rise even after 80 ns to levels around 0.3 nm.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…7 ). These results were consistent with the RMSD plots for furin-mozenavir, furin-folic acid, and furin-folinic acid complexes [ 94 , 96 ]. However, same observation cannot be said about the unbound protein as the RMSD continued to rise even after 80 ns to levels around 0.3 nm.…”
Section: Resultssupporting
confidence: 87%
“…The 29 compounds had binding energies ranging from − 9.0 to − 2.0 kcal.mol −1 [ 93 ]. Another study docked mozenavir with the furin protease using AutoDock and reported a binding energy of − 12.05 kcal.mol −1 as against the reference furin inhibitor decanoyl-RVKR-chloromethyl ketone which had a binding energy of − 6.89 kcal.mol −1 [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contact surface of ACE2 that binds to RBD has been chosen as the best active site of ACE2 receptor protein. [ 39 ] The important amino acids of ACE2 surface that binds with RBD area are ASP350, HIS401, PHE40, GLU375, TRP349, ASN394, LYS353, THR371, GLY326, ARG393, ARG514, and PRO399. With the help of AutoGrid, a grid box was formed in active site ACE2 receptor protein of 7DF4 with grid center coordinates X = 171.680; Y = 214.638; Z = 285.757.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%